The Civil War [videorecording (DVD)] / a Florentine Films production ; a film by Ken Burns. - Burns, Ken, 1953-; McCullough, David G. (Ken Burns, 1990)
The Civil War is the first full scale film history of the terrible conflict that tore the country apart and defined us as a nation. Discusses various battles and their impact on a divided country.